O-60 FAIR data management in exposome research – a case study from the EU-funded EXIMIOUS project. (14th March 2023) - Ghosh, Manosij; Broothaerts, Katrijn; Ronsmans, Steven; Roig, Ingrid Barcena; Scheepers, Jef; Dikmen, Mustafa; Ciscato, Emily Rose; Blanch, Carolina; Plusquin, Michelle; Nygaard, Unni C; Sejbæk, Camilla Sandal; Hougaard, Karin S; et al.
Abstract : EXIMIOUS is one of the nine H2020 exposome projects which is part of the European Human Exposome Network. As part of the EXIMIOUS project (Mapping Exposure-Induced Immune Effects: Connecting the Exposome and the Immunome) mostly constituted of researchers, we navigated the complex landscape of data protection and security, ethics and making data FAIR through our data management plan. While all projects (H2020, Horizon Europe and beyond) are obligated to conform to many of these regulations, researchers often lack the right tools and/or accurate understanding of the ethical/legal framework to independently address such challenges. More than 2 years into the project, we have successfully addressed many of these challenges. Through this elaborate exercise, we have acquired tools which allow us to make our research data FAIR, while at the same time ensuring data privacy and security (GDPR compliant). Herein we share our experience of creating and managing the data workflow through an open research communication, with the aim of helping other researchers build their data management framework in their own projects. Additionally we provide a checklist 'DMPCHECK' which the researchers can use to make their project data FAIR. Acknowledgement: This project has received funding from the European Union's Horizon 2020 research and innovation programme under grant agreement No 874707.